2014
DOI: 10.1002/cjg2.20093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Seismic Anisotropy of the Typical Slate from the Gaoligong Mountains, Yunnan Province, China

Abstract: Slate, as one of the low-degree metamorphic rocks, is widely distributed in China. Research on the seismic velocity of slate can help distinguish this kind of transitional rocks as well as understand anisotropy of the upper crust. This paper presents laboratory research on the seismic velocity of slate samples collected from the Bingzhongluo district of Yunnan Province, and part of the experiment was conducted at the Dalhousie High Pressure Laboratory, Canada. The laboratory testing yielded the seismic velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In crystalline low porosity rocks, the complete closure of microcracks at grain boundaries is observed in laboratory experiments at about ~200 MPa, which is equivalent to depths around 8 km (e.g. Christensen, 1985;Guo et al, 2014). In the case of slates from the WALZ, recent laboratory data have shown that the magnitude of the anisotropy increases with the decrease of confining pressure, as the orientation of the microcracks is strongly controlled by the shape fabric in very well foliated slates (Cárdenes et al, 2021).…”
Section: Radial Anisotropymentioning
confidence: 97%
“…In crystalline low porosity rocks, the complete closure of microcracks at grain boundaries is observed in laboratory experiments at about ~200 MPa, which is equivalent to depths around 8 km (e.g. Christensen, 1985;Guo et al, 2014). In the case of slates from the WALZ, recent laboratory data have shown that the magnitude of the anisotropy increases with the decrease of confining pressure, as the orientation of the microcracks is strongly controlled by the shape fabric in very well foliated slates (Cárdenes et al, 2021).…”
Section: Radial Anisotropymentioning
confidence: 97%